Pragmatic science? Reflections on the academic - industry interactions in a European aviation research programme - Nixon, Jim; Pilbeam, Colin; Kirwan, Barry (EDP Sciences, 2019)
In this article we explore the types of science produced and disseminated in human factors research in the cognitive domain. We reflect on the methods and techniques used in the European, Horizon 2020 Future Sky Safety Project: Human Performance Envelope (P6). This project has spanned multiple research paradigms successfully, and engaged academia and research organizations throughout. We discuss the challenges of conducting practically focused work that can also be brought to publication in peer-reviewed journals. Finally, we frame our research contributions within this project using a model of practitioner engagement.
Keywords: human factors; aviation; European project; publishing; Science